Kemarau di lembah : sajak-sajak dan cherpen-cherpen pilihan - Kassim Ahmad, 1933- (Pulau Pinang : Saudara Sinaran Berhad, 1967)
Short stories and poems in Malay; some poems with parallel translation in English.
mayeng
Koleksi Sumbangan: Dr. Syed Husin Ali.
Keywords: Malay fiction